The Leadership of the Principal of Madrasa in Implementing the Madrasa Tsanawiyah Al Ittihadiyah Curriculum Program at Pangkalan Masyhur Medan - Syafaruddin Syafaruddin; Salim Salim; Hamdan Hamdan (IAIN Padangsidimpuan, 2020)
This paper aims to explain the principal of the madrasa's leadership in implementing the curriculum program at Madrasa Tsanawiyah Al Ittihadiyah Pangkalan Masyhur Medan. This study used a qualitative method because it revealed madrasa principals' behavior, vice-principal of the madrasa, education staff, and teachers in implementing madrasa curriculum management. For data collection, this study used interview techniques, observation, and document review. The data were collected then analyzed using data reduction steps, data exposure, and concluding. Triangulation techniques were used to ensure the validity of the data, both among participants and between methods. This findings indicated that the madrasa principal's leadership in implementing the curriculum program at MTs Al Ittihadiyah Pkl. Mahsyur is performed effectively. It was indicated by (1) the communication carried out by the principal of the madrasa in socializing the vision, mission, goals, and development of the madrasa curriculum; (2) wise decision making by the principal of the madrasa in curriculum deliberations; (3) exemplary shown by the principal of the madrasa in efforts to develop curriculum; and (4) particular motivation given to teachers in madrasa curriculum development efforts.